PENGARUH TALENT MANAGEMENT TERHADAP EMPLOYEE RETENTION DENGAN EMPLOYEE ENGAGEMENT SEBAGAI MEDIASI PADA HOTEL AMARIS MAKASSAR - Saputra, Ade Cahya Prandy; Fajriah, Yana; Sohilauw, Muhammad Irfai (LP2M Universitas Bina Bangsa, 2025)
The purpose of this study was to determine the effect of Talent Management on Employee Retention with Employee Engagement as a mediator, where this study used a saturated sample with a census method for sampling, namely 45 samples. The research method used is structural equation model analysis with the help of smartpls software. The results of this study indicate that talent management has a positive and significant effect on employee retention, and employee engagement has a positive and significant effect mediating the influence between talent management on employee retention